Caracterização de usinas de reciclagem de entulho como agentes na gestão circular dos resíduos da construção civil - Frasson, Sueli Aparecida (2017)
Actions to reduce and implement means of disposal and treatment of waste generated by the construction industry are becoming more and more priorities and lead to studies aimed at new tools in the management and management of these. Within this context, Rubble Recycling Plants (RRP) have been shown to be one of these tools. With the potential to receive and recycle construction waste, these plants reduce the impact of the construction sector on the environment, as well as reinsert the waste in the production chain, adding value to it. Thus, this research presents the characterization of debris recycling plants as agents in the circular management of waste from the Civil Construction, based on the circular economy model. In addition to environmental gains, RRP also collaborate in the creation of formal jobs, in reducing waste disposal in inappropriate places and in stimulating the formation of a new productive chain, through the processes that transform the wastes into new aggregates for Civil Construction . It is concluded that there is still a lack of dissemination and clarification of the potential use of recycled waste in order to change the culture experienced by engineers, designers and the population. It was also identified that more laws and regulations are needed to determine the use of recycled material in the works, as well as greater awareness of generators to give the necessary attention to the problem of generation and treatment of the wastes.